Social water management issues related to six Costa Rican indigene communities (2019-2020) - Chacón Jiménez, Luz María (2022)
Objective: to provide a better understanding of the problems associated with the social management of water in six indigenous communities based on qualitative and quantitative data obtained during the 2020-2021 period. Methodology: a mixed and exploratory research was carried out in which qualitative and quantitative data were obtained. The qualitative data is the result of the workshops carried out within the framework of the research project B9314 “Social management of water in indigenous territories from Visual Sociology. Selected cases in the provinces of Puntarenas and Limón”; while water analyzes are quantitative results obtained from water quality analyses conduct in key spots identified by the community. Results: The analyzes carried out showed that 13 of the 15 water samples collected presented fecal contamination, of predominantly animal origin, however, contamination of anthropic origin was also observed. The workshops carried out in the community indicate that this contamination can be associated with a combination of environmental degradation factors, probably related to the usurpation of land by non-indigenous people, deforestation, population growth, pollution and the lack of effective protection policies. of water sources, both within the territories and at the institutional level, which is aggravated due to the limited effective action of the Costa Rican Institute of Aqueducts and Sewers to carry out actions to supply water for human consumption in the case studies. Conclusions: The problems associated with the social management of water in the communities under study are of a multicausal nature and for this reason require multidisciplinary training and support processes to improve the quality of life of indigenous populations.